State of illness-dependent associations of neuro-cognition and psychopathological syndromes in a large transdiagnostic cohort - Stein, Frederike; Schmitt, Simon; Brosch, Katharina; Meller, Tina; Pfarr, Julia-Katharina; Ringwald, Kai; Lemmer, Gunnar; Philipsen, Alexandra; Meinert, Susanne; Lemke, Hannah; Waltemate, Lena; Thiel, Katharina; et al. (Journal of affective disorders, 2023)
There is a lack of knowledge regarding the relationship between dimensional psychopathological syndromes and neurocognitive functions, particularly across the major psychiatric disorders (i.e., Major Depressive Disorder (MDD), Bipolar Disorder (BD), and Schizophrenia (SZ)). SANS, SAPS, HAMA, HAM-D, and YMRS were assessed in 1064 patients meeting DSM-IV-TR criteria for MDD, BD, SZ or schizoaffective disorder (SZA). In addition, a comprehensive neuropsychological test battery was administered. Psychopathological syndromes derived from factor analysis and present state of illness were used to explore psychopathology-cognition relationships. Correlational analyses were corrected for age, sex, verbal IQ, years of education, and DSM-IV-TR diagnosis. Age of onset and total duration of hospitalizations as proxies for illness severity were tested as moderators on the cognition – psychopathology relationship. The negative syndrome, positive formal thought disorder as well as the paranoid-hallucinatory syndrome exhibited associations with neuro-cognition in an illness state-dependent manner, while the psychopathological factors depression and increased appetite only showed weak associations. Illness severity showed moderating effects on the neurocognitive-psychopathology relationship only for the negative syndrome and positive formal thought disorder. No healthy control subjects were entered into the analyses because of lack of variance in psychopathological symptoms, which prevents from drawing conclusions regarding the relative level of potential cognitive impairments. This study suggests the relationship of neuro-cognition and psychopathology to be highly state of illness-dependent across affective and psychotic disorders. Results hint at the moderating effects of illness severity on psychopathological factors that might be more treatment resistant. •Psychopathological dimensions are correlated with distinct cognitive domains in a state-of-illness dependent manner•Positive formal thought disorder and the negative syndrome show largest correlations with cognitive domains•Illness severity moderates the association between psychopathology and cognition•Schizophrenia patients show most severe cognitive impairment compared to major depression and bipolar disorder